Singular integral equations analysis of THz wave scattering by an infinite graphene strip grating embedded into a grounded dielectric slab - Kaliberda, Mstyslav E; Lytvynenko, Leonid M; Pogarsky, Sergey A (Journal of the Optical Society of America. A, Optics, image science, and vision, 2019)
We consider the scattering and absorption of a plane H-polarized THz wave by an infinite periodic graphene strip grating embedded into a grounded dielectric slab. The problem is reduced to the dual series equations, which, in turn, are reduced to the singular integral equation with additional conditions. The numerical method of the solution is based on the Nystrom-type algorithm and has guaranteed convergence. We use the isotropic model of graphene with conductivity described by a scalar function obtained from Kubo formalism. The dependences of the absorption coefficient on the frequency as well as the near-field distribution are presented. They show a variety of plasmon and grating-mode resonances, which are identified and studied. Almost perfect absorption is obtained near these resonances.We consider the scattering and absorption of a plane H-polarized THz wave by an infinite periodic graphene strip grating embedded into a grounded dielectric slab. The problem is reduced to the dual series equations, which, in turn, are reduced to the singular integral equation with additional conditions. The numerical method of the solution is based on the Nystrom-type algorithm and has guaranteed convergence. We use the isotropic model of graphene with conductivity described by a scalar function obtained from Kubo formalism. The dependences of the absorption coefficient on the frequency as well as the near-field distribution are presented. They show a variety of plasmon and grating-mode resonances, which are identified and studied. Almost perfect absorption is obtained near these resonances.